Multidrug-Resistant Tuberculosis and Implementation of Control Measures in Ketapang District, West Borneo, Indonesia - Imelda Nita Saputri; Eva Lydia Munthe (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Background: Multidrug-resistant Tuberculosis (MDR-TB) has emerged as a threat of public health in Indonesia. The utilization of GeneXpert MTB/RIF as a rapid yet effective diagnostic tool enables early and appropriate treatment initiation of MDR-TB. This study aims in describing the occurrence of MDR-TB and the implementation of control measures in Ketapang District, West Borneo, Indonesia, since the utilization of GeneXpert MTB/RIF as a diagnostic tool. Methods: This is a cross-sectional descriptive study. The data were taken from medical record of patients with MDR-TB in Dr.Agoesdjam District General Hospital. The diagnosis was obtained from PCR-based analysis GeneXpert MTB/RIF of sputum sample, which detected Mycobacterium tuberculosis resistant to Rifampicin. Results: Seventeen subjects were included in the study. Subjects were 8 (47%) male and 9 (53%) female aged 24-75 years. Most subjects are farmers (35.3%) or housewives (35.3%), and did not receive formal education (41.2%). The main symptom reported upon admission was cough (41.2%). Direct microscopic smear of sputum detected acid-fast bacilli of +2 (29.4%) and +1 (29.4%) the most. The most common feature seen in thoracic X-ray was infiltrate in 100% of cases. Four subjects (23.5%) have type II diabetes mellitus, while one subject (5.9%) is infected with HIV. Subjects are categorized into new case (17.6%), failure of category 1 treatment (41.2%), and failure of category 2 treatment (41.2%). Treatment for MDR-TB has been initiated since 2014, while two subjects have not started taking the regimen. Among 15 subjects receiving treatment, one (6.7%) was recovered, 6 (40%) subjects deceased, and 8 (53.3%) subjects are currently still taking the regimen, while conversion occurred in 8 (53.3%) subjects. Conclusion: Using the GeneXpert MTB/RIF analysis, 17 cases of MDR-TB have been detected in Ketapang district. Management of MDR-TB has been conducted since 2014.